2006
DOI: 10.1128/jb.00369-06
|View full text |Cite
|
Sign up to set email alerts
|

GlpD and PlsB Participate in Persister Cell Formation in Escherichia coli

Abstract: Bacterial populations produce dormant persister cells that are resistant to killing by all antibiotics currently in use, a phenomenon known as multidrug tolerance (MDT). Persisters are phenotypic variants of the wild type and are largely responsible for MDT of biofilms and stationary populations. We recently showed that a hipBA toxin/antitoxin locus is part of the MDT mechanism in Escherichia coli. In an effort to find additional MDT genes, an E. coli expression library was selected for increased survival to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
170
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 51 publications
4
170
0
Order By: Relevance
“…PlsB converts G3P to 1-acyl-G3P, an essential precursor of the phospholipid biosynthesis pathway (Lin, 1976). Possibly, these enzymes affect persister formation or resuscitation by modulating cellular G3P levels (Spoering et al, 2006). If and how these findings are connected to fosfomycin resistance remains to be determined.…”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…PlsB converts G3P to 1-acyl-G3P, an essential precursor of the phospholipid biosynthesis pathway (Lin, 1976). Possibly, these enzymes affect persister formation or resuscitation by modulating cellular G3P levels (Spoering et al, 2006). If and how these findings are connected to fosfomycin resistance remains to be determined.…”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…Screening of an E. coli overexpression library led to the discovery of glpD and plsB as persistence genes (Spoering et al, 2006). GlpD is a G3P dehydrogenase involved in the catabolism of glycerol.…”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…(The genetic bases for senescence and persistence are just beginning to emerge; see, for example, Nystrom, 2005;Vásquez-Laslop et al, 2006;Spoering et al, 2006. ) In reference to the third assumption, we can interpret cell division as a new, youthful cell being born from an old one.…”
Section: Persisters Have a Number Of Interesting Characteristicsmentioning
confidence: 99%
“…As De Groote et al (2011) note, their finding implicating an organic phosph[on]ate in persistence formation may be related to the observation that deletion of the E. coli gene glpD, encoding sn-glycerol-3-phosphate dehydrogenase, leads to a reduction in persistence (Spoering et al, 2006). In the glpD deletion strain, it appears that high levels of G3P (caused by lack of catabolism by GlpD) plus derepression of the Glp regulon (which is induced by G3P interacting with the GlpR repressor of the regulon) lead to suppression of the formation or maintenance of persisters.…”
Section: A Persistent Problemmentioning
confidence: 99%
“…Perhaps the putative organic phosph[on]ate promoter of persistence does so by competing with G3P in its role of reducing persistence, for example by preventing its interaction with GlpR. However, Spoering et al (2006) found that, in E. coli, deletion of glpT (which is part of the Glp regulon) does not reduce persistence (Spoering et al, 2006) as it does in P. aeruginosa (De Groote et al, 2011). But this may be explained by the fact that, in E. coli, there are several possible transporters for G3P, with Ugp being the main transporter for G3P under phosphate starvation conditions (Xavier et al, 1995), while in P. aeruginosa, GlpT is likely to be the only transporter for G3P, as no orthologues for ugpA or ugpB are found in P. aeruginosa.…”
Section: A Persistent Problemmentioning
confidence: 99%